(untitled) (Research, Society and Development, 2022)
The objective of the study was to assess the prevalence of anxious, depressive and stress symptoms, as well as the consumption of antidepressants and anxiolytics among young adults during the COVID-19 pandemic in Brazil. This is a cross-sectional study conducted online via social media involving individuals between 18 and 35 years old. Participants answered a sociodemographic questionnaire and were asked about the use of anxiolytics and antidepressants. Mental health was assessed using the DASS-21 scale. The sample was composed of 349 participants of both sexes, and 71 (20.3%) used antidepressants and/or anxiolytics during the pandemic. Of these, 20.5% used anxiolytics, 31.8% used antidepressants, and 28.4% used both concomitantly. The main anxiolytic drug reported was clonazepam, and the antidepressant, fluoxetine. About mental health, a prevalence of 27.5% anxious symptoms, 31.8% depressive symptoms, and 30.7% stress symptoms was found. The results also show that the prevalence of depressive symptoms and stress reached 51.3% and 50.0%, respectively, in the participants who, prior to the pandemic, were already using medication for depression control, while in the participants who reported taking medication for anxiety control prior to the pandemic, the prevalence of anxious symptoms was 61.0%, depressive 56.4%, and stress 57.1%. Thus, high prevalence of mental disorders and use of medications were found, and such findings serve as an alert for the development of specific interventions.